Study on the Instability Characteristics and Bolt Support in Deep Mining Roadways Based on the Surrounding Rock Stability Index: Example of Pansan Coal Mine - Jucai Chang; Kai He; Zhiqiang Yin; Wanfeng Li; Shihui Li; Dongdong Pang (Advances in Civil Engineering)
In view of the influence of mining stress on the stability of the surrounding rock of inclined roof mining roadways in deep mines, the surrounding rock stability index is defined and solved based on the rock strength criterion and the stress distribution. The mining roadway of the 17102(3) working face of the Pansan Coal Mine is used as the engineering background and example. The surrounding rock’ stabilities under the conditions of no support and bolt support are analyzed according to the surrounding rock’s stability index and the deformation data. The results show that the areas of low wall and high wall instability are 1.68 m2 and 2.12 m2, respectively, and the low wall is more stable than the high wall; the areas of the roof and floor instability are 0.33 m2 and 0.35 m2, respectively, and the roof and floor are more stable than the two sides. During mining, the area of instability greatly increases at first, then decreases to 0, and reaches a maximum value at the peak of the abutment pressure. The stability of the surrounding rock decreases first and then increases. Compared with the end anchoring bolt support, the full-length anchoring bolt support reduces the area of instability to a greater extent, and the full-length anchoring bolt support effect is better. The surrounding rock in the end anchoring zone and the full-length anchoring zone began to deform significantly at 200 m and 150 m from the working face, respectively. This indicates that the control effect of the full-length anchoring bolt support is better and verifies the rationality of the surrounding rock stability index to describe the instability characteristics. This research method can provide a theoretical reference for analysis of the stability characteristics and support design of different cross-section roadways.